2011
DOI: 10.1039/c0cp01428a
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric mobile water

Abstract: In molecular dynamics simulations single-domain ferroelectric water is produced under ordinary ambient conditions utilizing carbon nanotubes open to a water reservoir. This ferroelectric water diffuses while keeping its proton-ordered network intact. The mobile/immobile water transitions and the step-wise changes in net polarization of water are observed to occur spontaneously. The immobile water becomes mobile by transforming into the single-domain ferroelectric water. Our general notion of relating a more hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…1; similar examples can also be found in Refs. [43,45]. For a temperature of 300 K there are only two conformational transitions connecting the three metastable states within the simulation time of 200 ns.…”
Section: Remd Simulations Of Water Confined Inside Cntsmentioning
confidence: 99%
“…1; similar examples can also be found in Refs. [43,45]. For a temperature of 300 K there are only two conformational transitions connecting the three metastable states within the simulation time of 200 ns.…”
Section: Remd Simulations Of Water Confined Inside Cntsmentioning
confidence: 99%
“…In recent years many theoretical and experimental efforts have been devoted to study CW in carbon nanotubes (CNTs). These studies are focused on various aspects such as water and proton conduction, water adsorption, formation of ice-nanotubes and water-nanotube in CNTs [1][2][3][4][5][6][7][8][9]. Some studies by high-resolution electron microscopy have revealed atomic scale interactions between the entrapped liquid phase and wetted graphite walls of CNTs [10].…”
Section: Introductionmentioning
confidence: 98%
“…It should be noted that a more recent MD study has reported a brand new water phase called 'ferroelectric mobile water (FMW)' (Nakamura & Ohno, 2011, 2012a, 2012b. Though the FMW at first sight appears similar to the immobilized water mentioned above, they are distinct from each other both in molecular structure and in dynamics.…”
Section: Introductionmentioning
confidence: 98%
“…Five independent phases, labeled '0' to '4', are suggested. Phase #4 corresponds to the FMW, the most stable phase (Nakamura & Ohno, 2011). Figure 12b shows unfolded-view snapshots from each phase, which is helpful to understand how the net polarization is digitized.…”
Section: Ferroelectric Mobile Water (Fmw)mentioning
confidence: 99%
See 1 more Smart Citation